(untitled) (American Journal of Islam and Society, 2023)
Kamran Bashir’s The Qur’an in South Asia addresses the question of how Sunni Muslims in India dealt with their intellectual heritage and identified with their past tradition in the wake of European colonialism and missionary activism. He focuses mainly on the Muslim scholars Sayyid Aḥmad Khān (d. 1898), Ashraf ʿAlī Thānawī (d. 1943) and Ḥamīd al-Dīn Farāhī (d. 1930), who wrote extensively on approaches to understanding the Qur’an after the mutiny/uprising that occurred in 1857 and the partition of India in 1947.